Quality properties of bihon-type cornstarch noodles blended with rice flour - Jim, Jamielou T. (College of Home Economics, University of the Philippines Diliman, 2019)
This study established the quality characteristics of cornstarch bihon-type noodles (CSN) and rice flour-blended cornstarch bihon-type noodles (CSN-RF) and its raw materials at the different material noodle stages of production. The analyses included proximate composition, physicochemical properties (pH, Aw, and amylose content), structural properties (Scanning Electron Microscopy (SEM) and Optical Microscopy), pasting properties (Rapid Visco-Analysis (RVA)), and thermal properties (Differential Scanning Calorimetry (DSC)). The CSN noodles were classified as both low acid (5.79±0.105) and with low Aw (0.38±0.016) with an amylose content of 31.27±0.25%. The CSN noodles were observed to have a smooth and dense structure as observed through SEM and optical microscope images. The CSN noodles had a similar pasting profiles with CSN-RF but obtained a lower final viscosity (1836.33cP) and setback viscosity (259cP) values as revealed by RVA analysis. The DSC curve of the CSN noodles was endothermic in all the material noodle stages. The CSN noodles had higher enthalpy values than CSN-RF during the gelatinized starch binder (41.70 J/g) and dough stages (210.01 J/g), but were lower during the dried (293.45 J/g) and cooked (457.75 J/g) stages. The peak temperatures obtained during the different material noodle stages were higher than 100°C, excluding the dried noodle material stage (< 75°C). The addition of RF to the base CSN noodle formulation at 40% w/w of total starch-flour mixture was observed to increase the protein (3.57±0.125%), fiber (0.27±0.205%) and ash (0.40±0.432%) content of CSN-RF relative to CSN noodles. The resulting CSN-RF noodles were also classified as both low acid (5.57±0.031) and with low Aw (0.47±0.028). The addition of RF to the base CSN noodles resulted in a less smooth surface and a more dense and complex structure due to the presence of extraneous plant matters as revealed by SEM and optical microscope images. An increase in setback viscosity (319.33cP) was obtained when RF was added to CSN as shown by its RVA pasting properties. All DSC curves were endothermic with increasing enthalpy as the level of processing increased. Higher peak temperatures were also obtained in the different material noodle stages relative to the raw materials. The information obtained from this study will benefit the different sectors involved in the noodle industry.